CLASS ACTION AGAINST THE NON-IMMEDIACY OF RATIFICATION OF THE 1990 MIGRANT WORKERS CONVENTION - Wisnu Aryo Dewanto (Fakultas Hukum Universitas Gadjah Mada, 2013)
Ratification of treaties in Indonesia can be regarded as mere political acts, as ratification itself does not yet rule for its enforcement in Indonesia’s jurisdiction. As stipulated in Article 11 of the 1945Indonesian Constitution, these ratifications are still subject to consent from the Indonesian House of Representatives (DPR) as they are the appointed institution in Indonesia with treaty-making powers. The act of ratification by the Indonesian Government is regarded as a ratification only in the international sense, where such action would only make the treaty enter into force internationally, but not internally within Indonesia. This paper seeks to analyze the legal implications which signatureand ratification of international treaties may hold in the Indonesian government. Such is done by studying the class action lawsuit for Indonesia being signatories the Convention on the Protection of the Rights of All Migrant Workers and Member of Their Families and its failure continue to further ratify the Convention. Ratifikasi perjanjian internasional merupakan tindakan politik yang memerlukan persetujuan dari Dewan Perwakilan Rakyat (DPR) sebagai lembaga dengan treaty-making power sebagaimana yangdiatur oleh Pasal 11 UUD 1945. Tindakan ratifikasi oleh Pemerintah Indonesia hanya bermakna sebagairatification hanya dalam the international sense, yakni membuat perjanjian tersebut berlaku di levelinternasional, bukan berlaku di wilayah hukum Republik Indonesia. Artikel ini menganalisis proses andimplikasi hukum diratifikasinya dan ditandatanganinya suatu perjanjian internasional oleh PemerintahIndonesia dengan menelaah gugatan class action yang dilakukan terhadap Pemerintah Indonesia mengenaibelum diratifikasinya Konvensi Buruh Migran.